Enterovirus-A71 exploits RAB11 to recruit chaperones for virus morphogenesis - Ng, Qing Yong (2024)
Background: Enterovirus 71 (EV-A71) causes Hand, Foot and Mouth Disease (HFMD) in children and has been associated with neurological complications. The molecular mechanisms involved in EV-A71 pathogenesis have remained elusive. Methods: A siRNA screen in EV-A71 infected-motor neurons was performed targeting 112 genes involved in intracellular membrane trafficking, followed by validation of the top four hits using deconvoluted siRNA. Downstream approaches including viral entry by-pass, intracellular viral genome quantification by qPCR, Western blot analyses, and Luciferase reporter assays allowed determine the stage of the infection cycle the top candidate, RAB11A was involved in. Proximity ligation assay, co-immunoprecipitation and multiplex confocal imaging were employed to study interactions between viral components and RAB11A. Dominant negative and constitutively active RAB11A constructs were used to determine the importance of the protein’s GTPase activity during EV-A71 infection. Mass spectrometry and protein interaction analyses were employed for the identification of RAB11A’s host interacting partners during infection. Results: Small GTPase RAB11A was identified as a novel pro-viral host factor during EV-A71 infection. RAB11A and RAB11B isoforms were interchangeably exploited by strains from major EV-A71 genogroups and by Coxsackievirus A16, another major causative agent of HFMD. We showed that RAB11A was not involved in viral entry, IRES-mediated protein translation, viral genome replication, and virus exit. RAB11A co-localized with replication organelles where it interacted with structural and non-structural viral components. Over-expression of dominant negative (S25N; GDP-bound) and constitutively active (Q70L; GTP-bound) RAB11A mutants had no effect on EV-A71 infection outcome, ruling out RAB11A’s involvement in intracellular trafficking of viral or host components. Instead, decreased ratio of intracellular mature viral particles to viral RNA copies and increased VP0:VP2 ratio in siRAB11-treated cells supported a role in provirion maturation hallmarked by VP0 cleavage into VP2 and VP4. Finally, chaperones, not trafficking and transporter proteins, were found to be RAB11A’s top interacting partners during EV-A71 infection. Among which, CCT8 subunit from the chaperone complex TRiC/CCT was further validated and shown to interact with viral structural proteins specifically, representing yet another novel pro-viral host factor during EV-A71 infection. Conclusions: This study describes a novel, unconventional role for RAB11A during viral infection where it participates in the complex process of virus morphogenesis by recruiting essential chaperone proteins.